Private Investment and Public Investment: Total Rates of Return and Global Balances in the OECD - António Afonso; José Alves; Sofia Monteiro (CESifo GmbH, 2025)
We assess the relevance of macro rates of return on time-varying fiscal and external sustainability. First, we compute the total public and private macroeconomic rates of return for 16 OECD countries from 1980 to 2022. We find that there is a positive impact of higher investment returns on stimulating higher aggregate demand, therefore resulting in higher tax revenues, which in turn lead to greater fiscal sustainability and more external sustainability by lowering the need for foreign capital and imports of goods and services. Accordingly, we demonstrate that macroeconomic rates of return of both public and private investment positively contribute to fiscal sustainability and that public sector investment also displays the same positive effect on external sustainability.
Keywords: E22; F41; H54; H61; 330; macroeconomic rates of return; fiscal sustainability; external sustainability; time-varying; public investment; private investment